CALITATEA AGROALIMENTARĂ – DIMENSIUNE A LIBERTĂȚII DE CONȘTIINȚĂ. EVIDENȚE DIN MONTANOLOGIA MONDIALĂ, EUROPEANĂ ȘI ROMÂNEASCĂ (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Agri-food Quality – A Dimension of Freedom of Conscience. Evidence from World, European and Romanian MontanologyThe article develops the issue of agri-food quality in the current context of diluting freedoms of conscience. Human development increasingly depends on providing the necessary food, both in terms of quantity and quality. Quantitatively, many of the food safety and security issues have been addressed. Qualitatively, there are still many problems to be solved, such as: healthy nutrition, quality nutrition, food education, etc. Due to the stress and challenges they are subjected to, more and more individuals of the 21st century no longer feed themselves qualitatively, but only cover emotions or an insufficient nutritional minimum for human health. Current research summarizes a number of concepts associated with agri-food quality and healthy nutrition in the context of freedom of choice. The research is mainly exploratory, synthesized from the literature and data proccesed from World Bank and Eurostat. Data from the world, European and Romanian montanology are brought to attention, as well as the revealed comparative advantage indicator of the complex of food classes so that the paper offers a faithful image of Romania’s position in the world agri-food conjuncture.